Research on dependencies in simulated DNA sequences - Rekašius, Tomas (Lietuvos matematikos rinkinys, 2005)
Many publications in bio-informatics deal with long-range correlation of nucleotides in DNA sequences, which implies that such sequences are complicated systems with hierarchical structure. Applying the method of simulation, this work reveals that long-range correlation might develop in the course of evolution of a sequence under very general rules.